Energy Efficiency Evaluation of a Continuous Treatment of Agroforestry Waste Biomass by Hydrothermal Carbonization [Evaluacion de la Eficiencia Energetica de Un Proceso Continuo de Tratamiento de Residuos Agroforestales Mediante Carbonizacion Hidrotermica] - Diaz-Robles, L; Vallejo-Gallardo, F (Universidad del Bio-Bio, 2021)
Among the processes available to treat waste biomass, the thermal conversion with water in subcritical conditions, called Hydrothermal Carbonization, is being studied in deep the last years. Hydrothermal Carbonization needs lower temperatures than other thermal processes, and a solid with high energy density and hydrophobic properties are obtained. This work presents the modeling and simulation of continuous operation of the Hydrothermal Carbonization process for two residual biomasses: Pinus radiata sawdust from the wood industry and rapeseeds (Brassica napus) as industrial waste. The analysis was performed evaluating the whole process, from mixing the raw biomass with water and the reaction until obtaining the final pellet. All unit operations were modeled with phenomenological equations. The Higher Heating Value and the Mass Yield of the reaction were estimated by Multiple Linear Regression equations, using as an explanatory variable the Polarity Index, the Reactivity Index, the Severity Factor, and the Biomass: Water Ratio. The best model had an adjusted determination coefficient (R2a) of 0,90. Finally, the process presented an energy efficiency greater than 72% for sawdust and 77 % for rapeseed. Therefore, Hydrothermal Carbonization must be considered as an alternative to valorize agroforestry waste biomass to an industrial scale. © 2021. All rights reserved.